2012
DOI: 10.1007/s00231-012-0993-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation for frost properties on a cold cylinder surface in cross flow

Abstract: An experimental study was reported earlier on the development of frost formation by humid flow passing over the cylinder. In this study, dimensionless correlations based on previous experimental data and reported empirical correlations of others for frost properties are proposed. The frost conduction coefficient is determined by using an analytical equation. Subsequently, correlations are sought for the heat conduction coefficient, dimensionless temperature, dimensionless thickness and density. The advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Yang and Lee [7] proposed the correlation for the frost layer thickness and the dimensionless frost density on a cold plate. Recently Barzanoni et al [8] proposed in a study, a dimensionless correlations based on previous experimental data and reported empirical correlations of others for frost properties. The frost conduction coefficient is determined by using an analytical equation.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Lee [7] proposed the correlation for the frost layer thickness and the dimensionless frost density on a cold plate. Recently Barzanoni et al [8] proposed in a study, a dimensionless correlations based on previous experimental data and reported empirical correlations of others for frost properties. The frost conduction coefficient is determined by using an analytical equation.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Lee [7] proposed the correlation for the frost layer thickness and the dimensionless frost density on a cold plate. Recently Barzanoni et al [8] proposed in study, of dimensionless correlations based on previous experimental data and reported empirical correlations of others for frost properties are proposed. The frost conduction coefficient is determined by using an analytical equation.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Lee [7] proposed the correlation for the frost layer thickness and the dimensionless frost density on a cold plate. Recently Barzanoni et al [8] proposed in study, dimensionless correlations based on previous experimental data and reported empirical correlations of others for frost properties are proposed. The frost conduction coefficient is determined by using an analytical equation.…”
Section: Introductionmentioning
confidence: 99%